The Effect of Environmental Performance on Financial Performance with Good Corporate Govermance as a Moderating Variable in Mining Companies Listed on the Indonesia Stock Exchange Period 2017-2020 - Ayu, Baiq Dinda Puspita; Ajiani, Ika Putri Fitri (Universitas Nusantara PGRI Kediri, 2023)
Research aim : This study aims to prove that good corporate governance can strengthen the influence of environmental performance on the financial performance of mining companies. Design/Method/Approach : This research is an explanatory research to test a theory or hypothesis to strengthen or even reject the theory or hypothesis of existing research results and the approach used is a quantitative approach. The population in this study is mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This research sample used the puposive sampling method and obtained 13 companies in (one period) that met the criteria. The data analysis method used in this study was processed using SPSS software version 25. Research Finding : The results showed that good corporate governance can strengthen the influence of environmental performance on the financial performance of mining companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -